Literary translation and the rediscovery of reading - Scott, Clive, 1943- (Cambridge : Cambridge University Press, 2012)
'The act of translation is perhaps the ultimate performance of reading. By translating a text translators rework the source text into a reflection of their reading experience. In fact all reading is translation, as each reader incorporates associations and responses into the reading process. Clive Scott argues that the translator needs new linguistic resources to do justice to the intricacies of the reading consciousness, and explores different ways of envisaging the translation of a literary work, not only from one language to another, but also from one form to another within the same language. With examples drawn from different literatures, including English, this exciting new departure in translation theory has much to offer to students of literature and of comparative literary criticism. It also encourages all readers of literature to become translators in their turn, to use translation to express and give shape to their encounters with texts'--
Introduction -- 1. Reading and translation -- 2. Reading: voice and rhythm -- 3. Translating the textual environment (1) -- 4. Translating the textual environment (2) -- 5. Translating the acousticity of voice -- 6. Free verse and the translation of rhythm -- 7. The reinvention of the literary in literary translation -- 8. Writing and overwriting the sound of the city -- Epilogue: portrait of a reader: Malcolm Bowie in search of the critical interworld.
Includes bibliographical references (pages 213-222) and index.
Keywords: Translating and interpreting; Literature -- Translations -- History and criticism; Reading, Psychology of